The Relationship between Knowledge and Personal Hygiene Behavior of Menstrual in Adolescent Girls at SMP Negeri 1 Sukamaju Selatan - Andi Ulfiana Fitri; Iluh Yuliantari; Meliana Handayani (Journal of Scientific Insights, 2026)
Personal hygiene plays an important role in improving health through proper hygiene practices during menstruation. Most adolescents do not yet understand how to perform personal menstrual hygiene correctly, including when to change sanitary pads and how to clean them. This occurs due to the lack of education on menstrual hygiene in the family and school environment, combined with limited access to clean water and inadequate sanitation facilities at school, as well as minimal and poorly structured reproductive health and menstrual hygiene education. This study aims to determine the relationship between knowledge and personal menstrual hygiene behavior among adolescent girls at SMP Negeri 1 Sukamaju Selatan. This study used a quantitative method with a cross‑sectional design. The sample consisted of 147 respondents selected using total sampling technique. Data were collected using a questionnaire and analyzed using the Chi‑Square test. The results showed a significant relationship between adolescent girls’ knowledge of personal menstrual hygiene and their behavior in practicing personal menstrual hygiene. The Chi‑Square test yielded a significance value (p) of 0.000, which is smaller than 0.05, indicating that the relationship is statistically significant at a 95% confidence level. There is a relationship between knowledge and personal menstrual hygiene behavior among adolescent girls at SMP Negeri 1 Sukamaju Selatan.